Structural response and energy extraction of a fully passive flapping foil. (July 2017) - Wang, Zhuo; Du, Lin; Zhao, Jisheng; Sun, Xiaofeng
Abstract: The structural response and energy extraction of a foil undergoing two-degree-of-freedom fully passive flapping motions in a two-dimensional flow are numerically investigated at R e = 400 . The simulations of the fluid–structure interaction were conducted using the Immersed Boundary Method (IB Method). In the parametric space of flow reduced velocity and pivot location investigated, five response regimes are identified. This paper focuses on the stable synchronisation regime, which is characterised by harmonic wake-body synchronisation with stable large-amplitude oscillations. Correspondingly, a novel wake pattern composed of a triplet of vortices and a pair of vortices shed per cycle, referred to as T+P pattern, is encountered. An analysis of the dynamic nonlinearity showed that the inertia forces can induce perturbations in the form of harmonics to the dynamics of the system. Furthermore, the highest cycle-averaged power output coefficient and efficiency were found to be C ̄ P = 0 . 95 and η = 0 . 32, respectively. The present results suggest that high-efficiency case in fully passive flapping motions is associated with a large pitch–plunge phase and a 2S wake pattern composed of two strong single LEVs shed per cycle.